KEMITRAAN ORANGTUA DAN GURU DALAM MEMBANGUN PERILAKU HIDUP BERSIH DAN SEHAT ANAK USIA 5 - 6 TAHUN DI RA AL- IZZAH KOTA SERANG - Tasya Saskia; Imroatun; Uyu Mu’awwanah (Cakrawala Pedagogik, 2026)
This study aims to determine the partnership between parents and teachers in building Clean and Healthy Behavior (PHBS) for early childhood aged 5 - 6 years at RA Al-Izzah, Serang City. This study uses a qualitative descriptive approach with data collection methods through observation, interviews, and documentation. The research subjects included the principal, one Class B teacher, and five parents, with details of three boys and two girls. The study focused on forms of partnership between parents and teachers in educating children to apply clean and healthy behaviors, such as washing hands with soap, maintaining personal and environmental hygiene, consuming nutritious food, and getting used to light exercise. The results show that the partnership between parents and teachers at RA Al-Izzah has run well and effectively, as reflected in the active involvement of parents in school activities, intensive communication between teachers and parents, as well as the consistent habituation of clean and healthy behavior at school and at home. Nevertheless, there are still some obstacles, such as the lack of motivation of some children and limitations of certain infrastructure. Overall, this partnership contributes significantly to increasing children's awareness of the importance of personal and environmental hygiene as part of character building for health from an early age.